Biochar-based Composites : Preparation, Characterization and Applications - Showkat, Ahmad Bhawani (Springer, 2025)
This book provides solid, quantitative descriptions and reliable guidelines, reflecting the maturation and demand of the field and the development of biochar-based composites. This book summarizes the fundamental approaches and principles to prepare biochar-based composites. This book focuses on some important materials (metal oxide/hydroxide, magnetic, clay minerals, graphene oxide, etc.) used for the production of the composites. The coverage of book highlights the most exciting applications of biochar-based composites in the removal of organic and inorganic contaminants from waste water. The book is useful for the academics and researchers who are interested in the development biochar-based composites with background in material science, chemical engineering, environmental engineering and environmental chemistry.